Clinical Characterization of Children and Adolescents with Disorders of Sex Development Atending a Tertiary Centre in the Western Cape, South Africa - Manu, Ewuraa (Department of Paediatrics and Child Health, 2025)
Background: The objectives of our study were to describe the presentation, classification, and underlying causes, where possible, of Disorders of Sex Development (DSD) cases in a middleincome country in Africa. Methods: This was a retrospective review of all DSD cases referred to a Paediatric Endocrine unit in a tertiary hospital in South Africa from January 2006 to December 2021. The biochemical data were adjusted based on the reference range applicable to the chronological age and chromosomal sex. Results: Of the 139 patients analysed, 70 (50.4%) were 46, XY DSD, 46 (33.1%) were 46, XX DSD, and 23 (16.5%) were sex chromosome DSD. The mean adjusted testosterone (AT) at presentation did not differ between 46, XX DSD [AT: 0.4 (0.10-0.80)] and 46, XY DSD [AT: 0.4(0.10-1.05)]; p=0.76. Male sex was assigned at birth to 78 (67.2%) of both 46, XY, and 46, XX DSD groups. Of these, 73 (93.6 %) were assigned male gender of rearing. A precise diagnosis beyond a defect of androgen synthesis or action could not be made in 48 (68.6%) of the 46, XY DSD group. In contrast, 42 (91.3%) of the 46, XX DSD group had a precise diagnosis; 27 (64.3%) had ovotesticular DSD, 8 (19.0%) congenital adrenal hyperplasia (CAH), 5(12.0%) testicular DSD, and 2(4.7%) gonadal dysgeneses. Conclusion: In our cohort, 46, XY DSD predominated. Concordance between the sex assigned at birth and the gender of rearing after evaluation was 79.1%. The mean AT did not discriminate between various DSD categories. Ovotesticular DSD was the most common diagnosis among 46, XX DSD, and the reasons for this need to be explored.